Sustainable Conservation Management System for The Critically Endangered Betta Persephone in Ayer Hitam Peat Swamp Forest Reserve Muar Johor - Mujilan, Mohd Rafiq; Mohamad Abdullah, Nazirah; Kamar Supardi, Izyan Hakimah; Mohd Bukari, Saifullizan (International Journal of Integrated Engineering, 2023)
In recent years, there has been a lot of interest in protecting and conserving wildlife on a wide range of scales. Betta Persephone’s habitat life may be affected by urbanization in Ayer Hitam Peat Swamp Forest Reserve (AHPSFR). This species is endangered due to the widespread conversion of peat swamp forests to industrial forestry and monoculture plant. The evaluation of fish habitat always has been a research priority for individuals in the domains of environmental protection and sustainable development, to improve habitat conservation. Results of the study through sample water collection shows the result of pH water. Based on these environmental factors, the factors that under dry leaves and branches and blackwater are the main factors that affect Betta Persephone choose AHPSFR as its own natural habitat. The satellite data and to analyze the catchment area results and construct the maps. U.S Geological System (USGS) and Geographic Information System (GIS) used to generate the maps. Geographic Information System (GIS) is a computer system that analyses and displays information that is geographically referenced. This study is carried out to predict the hydrologic analyze of the study area. The location of Betta is at one of the small sub catchments at the study area. The sub catchment that are found of the habitat are at the nearly the low stream links and at the watershed area that are found using the software.